Intelligent virtual system for underwater vehicle piloting using Unity - Chin, Cheng Siong (Boca Raton, FL : CRC Press, 2020)
"This book supports the readers in the development of remotely operated vehicle (ROV) pilot training simulator by exploiting open source or free gaming software and the importance of using established and widely available games design techniques in providing engaging scenarios for the ROV training developers and trainees. There is no such book to guide the users to create an open-source virtual simulator for pilot training in the marine and offshore industry. The book can be used as a reference book for undergraduate and postgraduate, engineers, researchers, and lecturers in VR simulation using UnityTM as the leading software"--
OCLC-licensed vendor bibliographic record.
Keywords: Unity (Electronic resource); Autonomous underwater vehicles; Remote submersibles; Intelligent control systems